IMPLEMENTASI AKAD MUDHOROBAH PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAITUL MAAL WATTAMWIL “BINAMA” SEMARANG - Diah Sasikirana Retno Murniati; Muhammad Junaidi (Universitas Semarang, 2017)
ABSTRACTAlthough BMT (Baitul Maal wat Tamwil) has not had legal peotection, but in its principle these BMT institutions have performed their function asintermediary institutions that manage funds from, for and by the society. Theproblem of Bmt is not only limited to the legal legality that protect them, but alsorelated to the law of guarantee. Based on the above background, the writer formulates the purpose ofwriting, namely To know the Implementation of Mudharabah Agreement in KSPSBaitul Maal Wattamwil